2018
DOI: 10.3791/56798
|View full text |Cite
|
Sign up to set email alerts
|

Intracavernosal Pressure Recording to Evaluate Erectile Function in Rodents

Abstract: Erectile dysfunction (ED) is defined as the inability to attain or keep an erection of the penis, and this has become a prevalent male sexual disorder. Rodents are employed by many studies to research the physiology/pathology of erectile function. Erectile function in rodents can be evaluated by measuring the intracavernosal pressure (ICP). In practice, ICP can be monitored following electrical stimulation of the cavernous nerves (CNs). The arterial pressure of the carotid artery (the mean arterial pressure) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…RhoA and ROCK2 in rat cavernosum tissues showed decreased expression after intervention with HJI, but the expression of ROCK1 was not significantly affected by our treatment. As the most commonly used index for evaluating erectile function [32], the ICP indicated that HM and HH treatments did not fully improve erectile function to normal levels. HJI plays a role in the partial pathogenesis of BCNI-induced ED; however, HJI may achieve better therapeutic effects if it is combined with PDE5i drugs or other clinical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA and ROCK2 in rat cavernosum tissues showed decreased expression after intervention with HJI, but the expression of ROCK1 was not significantly affected by our treatment. As the most commonly used index for evaluating erectile function [32], the ICP indicated that HM and HH treatments did not fully improve erectile function to normal levels. HJI plays a role in the partial pathogenesis of BCNI-induced ED; however, HJI may achieve better therapeutic effects if it is combined with PDE5i drugs or other clinical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Erection function in rodents can be evaluated by measuring ICP [ 25 ]. The magnitude of erectile activity was quantified as the ratio of ICP to MAP, which is the common functional index to determine erectile function.…”
Section: Resultsmentioning
confidence: 99%
“…The mean arterial pressure (MAP) is used as a reference for ICP. Using ICP recording protocols, many key parameters of erectile function can be measured from the ICP response curve 15 . Figure 6 shows the mean maximum ICP ( Impairments of sperm quantity and quality after EHS onset.…”
Section: Increased Plasma Levels Of Stress Hormones Multiple Organ Dmentioning
confidence: 99%